1977
DOI: 10.1002/ajpa.1330460316
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory function and post‐pleistocene evolution in Nubia

Abstract: The present research focuses on craniofacial variation in Nubia over approximately 10,000 years. Samples were grouped according to their temporal location and subsistence pattern, and represent a transition from a hunting-gathering adaptation (Mesolithic) to a transitional hunting-gathering-agricultural adaptation (A-C Group) and finally to a fully agricultural adaptation (Meroitic/X-Group/Christian). The purposes were: (1) to compare the Mesolithic sample with the later Nubian populations; and (2) to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
161
2
5

Year Published

1979
1979
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(189 citation statements)
references
References 22 publications
21
161
2
5
Order By: Relevance
“…Through time, the vault became more rounded and anteriorly placed, the face more inferiorly placed, and the skull relatively shorter, with more posteriorly located masseter and temporalis muscles. In agreement with Greene's earlier analysis of the dental evidence, Carlson (1976a, b) and Carlson and Van Gerven (1977) concluded that the total pattern of dental reduction and reorientation of face and vault was the result of a reduction in masticatory stress associated with the transition from Mesolithic to Neolithic subsistence patterns. Although the mechanisms by which that morphological trend came about cannot be determined precisely, the most reasonable explanation emphsizes progressive alterations in maxillomandibular growth in response to developmental variation in the size and position of the muscles of mastication, i.e., the masticato7y-functional hypothesis (see Figure 2) (Carlson 1976b;Carlson and Van Gerven 1977).…”
Section: Alternatives To Biological Dz;ffusionismsupporting
confidence: 78%
See 3 more Smart Citations
“…Through time, the vault became more rounded and anteriorly placed, the face more inferiorly placed, and the skull relatively shorter, with more posteriorly located masseter and temporalis muscles. In agreement with Greene's earlier analysis of the dental evidence, Carlson (1976a, b) and Carlson and Van Gerven (1977) concluded that the total pattern of dental reduction and reorientation of face and vault was the result of a reduction in masticatory stress associated with the transition from Mesolithic to Neolithic subsistence patterns. Although the mechanisms by which that morphological trend came about cannot be determined precisely, the most reasonable explanation emphsizes progressive alterations in maxillomandibular growth in response to developmental variation in the size and position of the muscles of mastication, i.e., the masticato7y-functional hypothesis (see Figure 2) (Carlson 1976b;Carlson and Van Gerven 1977).…”
Section: Alternatives To Biological Dz;ffusionismsupporting
confidence: 78%
“…In agreement with Greene's earlier analysis of the dental evidence, Carlson (1976a, b) and Carlson and Van Gerven (1977) concluded that the total pattern of dental reduction and reorientation of face and vault was the result of a reduction in masticatory stress associated with the transition from Mesolithic to Neolithic subsistence patterns. Although the mechanisms by which that morphological trend came about cannot be determined precisely, the most reasonable explanation emphsizes progressive alterations in maxillomandibular growth in response to developmental variation in the size and position of the muscles of mastication, i.e., the masticato7y-functional hypothesis (see Figure 2) (Carlson 1976b;Carlson and Van Gerven 1977). More specifically, according to that hypothesis, the change in diet associated with the transition from the Mesolithic through the Christian periods in Nubia brought about a reduction in required neuromuscular activity for the muscles of mastication and thus a decrease in the stress placed on the teeth and jaws.…”
Section: Alternatives To Biological Dz;ffusionismsupporting
confidence: 78%
See 2 more Smart Citations
“…Dental crowding and malocclusion are often discussed in relation to the adoption of agriculture and the introduction of soft foods as part of the masticatory-functional hypothesis (Carlson and Van Gerven, 1977;Corruccini, 1984;Corruccini et al, 1983;Larsen, 2015). In this discussion, malocclusion encompasses two distinct features: malalignment of the teeth (i.e., crowding) and malalignment of the jaws (i.e., overbite and underbite).…”
Section: Malocclusionmentioning
confidence: 99%